Pola Pengalaman Wisatawan Generasi Z di Destinasi Pariwisata Yogyakarta - Priyanto, Sabda Elisa; Malkhamah, Siti; Baiquni, Muhammad; Suprihanto, John (Jurnal Pariwisata Terapan, 2024)
Generation Z is the largest population in Indonesia. Many potentials can be explored from their behavior. The purpose of this study is to discover what the pattern of experiences before, during and after traveling from generation Z tourists in Yogyakarta tourism destinations. This research method uses a qualitative approach, with a sequential research design. Where the data will begin with quantitative in the form of questionnaires to generation Z tourists, then the results are confirmed by conducting interviews with tour guides, tour drivers, tourist attraction managers, tour and travel owners, the results are triangulated by conducting field observations, seeing the behavior of generation Z tourists at tourist attractions. The results found that psychocentric generation Z tourists have a pattern of Psychocentric Gen Z experience in Yogyakarta, starting with (1) dreaming, then (2) researching, (3) planning, (4) booking, (5) anticipating, (6) traveling to, (7) experiencing, (8) sharing, (9) remembering, and (10) evaluating.  Generation Z travelers who are allocentric have a pattern of (1) Researching. (2) traveling to Yogyakarta, (3) Enjoying traveling in Yogyakarta, (4) Enjoying the return trip, (5) sharing, (6) recalling tourism activities, and (7) evaluating. Meanwhile, midcentric generation Z tourists have an experience pattern of (1) dreaming, (2) researching (3) booking, (4) anticipating, (5) enjoying a trip to each tourist attraction. (6) Enjoying tourist activities at tourist attractions (7) sharing. (8) remembering, and (9) evaluating.